Prothrombin expression in cancer-derived cell lines - Dunjić, Sofija; Cumbo, Marija; Gvozdenov, Maja; Tomić, Branko; Pruner, Iva; Radojković, Dragica; Đorđević, Valentina (Archives of Biological Sciences, 2019)
Paper description: The relationship between cancer and thrombotic disorders has been known for over a century. Many studies have examined the role of thrombin in the etiology and progression of cancer. There are limited literature data on the expression of prothrombin, the precursor of thrombin, in cancer cell lines. We aimed to determine whether common cancer-derived cell lines express prothrombin. Herein we show that the Caco-2 cell line expresses prothrombin, while cell lines MCF-7, SK-BR-3, U-87 and U-251 do not. Our findings point to a possible link between prothrombin expression and different types of cancer. Abstract: The link between thrombotic disorders and cancer has been known for over 150 years, although the precise mechanism of this relationship has not yet been resolved. Current data show that thrombin has a significant role in cancer metabolism, invasiveness, adhesion and survival. However, data regarding the expression of the thrombin precursor prothrombin in various cancer cell lines are scarce. Therefore, it was our objective to determine whether common cancer-derived cell lines (Caco-2, MCF-7, SK-BR-3, U-87 and U-251) express prothrombin. The prothrombin RNA expression level was assessed by qPCR, and the presence of prothrombin was analyzed by Western blot analysis. Our results show that Caco-2 cells originating from colorectal adenocarcinoma express prothrombin, whereas other analyzed cell lines do not. Our results provide a background for further research into the role of (pro)thrombin in cancer etiopathology. https://doi.org/10.2298/ABS180829046D Received: August 29, 2018; Revised: September 27, 2018; Accepted: October 3, 2018; Published online: October 10, 2018 How to cite this article: Dunjić S, Cumbo M, Gvozdenov M, Tomić B, Pruner I, Radojković D, Đorđević V. Prothrombin expression in cancer-derived cell lines. Arch Biol Sci. 2019;71(1):49-54.